Tomato chlorotic dwarf viroid: an evolutionary link in the origin of pospiviroids - Singh, Rudra P.; Nie, Xianzhou; Singh, Mathuresh (Journal of General Virology, 1999)
Over 40 isolates of potato spindle tuber viroid (PSTVd) have been reported from potato, other Solanum species and greenhouse tomato. These isolates have sequence similarities in the range 95–99%. A viroid which caused chlorotic leaves and severe dwarfing of plants in greenhouse tomato crops was detected. The viroid was found to hybridize readily with PSTVd probes. It migrated faster than PSTVd in return-polyacrylamide gel electrophoresis and was not amplified in RT–PCR by a primer pair based on the lower strand of the central conserved region of PSTVd. Nucleotide sequencing of the viroid indicated that it is a circular RNA of 360 nt, with less than 90% sequence similarities with PSTVd isolates. The Variable domain (V) has less than 60% and the Terminal Right domain less than 90% sequence similarity, while the remainder of the molecule has greater than 97% similarity with PSTVd. Because of its less-than 90% sequence similarities, unique V domain, lack of seed-transmission and lack of cross-protection by PSTVd, the viroid from tomato is proposed to be a distinct viroid species (tomato chlorotic dwarf viroid; TCDVd) which also differs from two viroids infecting tomato in nature. TCDVd may be an evolutionary link in the development of crop viroids, with Mexican papita viroid as the ancestral viroid.